Evidence-based medicine: new in the search for evidence - E. V. Verbitskaya; D. Yu. Belousov; A. S. Kolbin (Izdatelstvo OKI, 2023)
The review is focused on discussing new trends in DM, rethinking the evidence base medicine with an emphasis on demonstrating the efficacy and safety of new therapeutic agents and medical technologies, from gene editing to AI algorithms. At the same time, clinical trials of drugs are also not standing still, there is active development, new approaches, methods and designs are being developed. The process of drug development, registration and market launch of any drug takes a significant period of time, requires high financial costs and human resources. The gold standard of evidence-based medicine was initially considered to be RCTs, but at the same time, they have objective disadvantages: limited sample, inability to control all factors; insufficient follow-up time,negative impact on participants, inability to determine cause-and-effect relationships; limited measurement methods, limited budget and others. This review discusses the trends in the methodology of clinical research. The active implementation of new designs such as Adaptive Clinical Trials, "Master" protocols including Umbrella Study, Basket Study, Platform Studies, Master Observational Trials and the increased use of Single Patient Trials (N-of-1 trials) are allowing studies to become more efficient, relevant and applicable to real-life health care practice settings and patient-centered. In the review, we also look at both the pros and cons of the expanded use of biomarkers and Digital Endpoints in clinical trials and virtual clinical trials, which use mathematical models to study patient heterogeneity and its impact on various therapeutic questions. The process of expertise and regulatory approval continues to slow down the entry of drugs into the pharmaceutical market. The review considers changes in the approaches of regulators (FDA, EMEA and Russian Ministry of Health) to the drug registration procedure. The COVID-19 pandemic and sanctions have led to the need to expand the list of drugs with authorized accelerated registration. However, accelerated registration raises many questions regarding the sufficiency of the level of evidence and safety. As we can see a deep synthesis and integration of all available data is needed to achieve the next generation of evidence-based medicine. The major challenge in the next two decades will be to exploit the potential of multidimensional evidence generation by extracting, collating and generating large data sets of natural course of disease, genomics and all other omics analyses, all published clinical trials, RWD to provide next generation evidence.